Returning home : A study on individual and organizational aspects affecting repatriate knowledge transfer - Orbinski, Sanna (My University, 2019)
During their expatriation assignments, repatriates have often gained skills and knowledge that can be beneficial to their company after their return. Gathering and sharing this knowledge can be referred to as repatriate knowledge transfer also known as RKT. Though RKT can be beneficial for a company battling in a global business environment, RKT is not researched extensively. Additionally, companies often tend to overlook the value repatriate knowledge can offer for them. Prior studies have argued that both organizational and individual level aspects affect RKT. Individual level aspects consists of ability and motivation. Organizational level aspects include career management, repatriation support, organizational culture and managerial attitudes. Moreover, prior studies have argued that RKT often depends on repatriates’ own motivation and efforts to actively find and utilize RKT opportunities. Organizational level aspects can enhance repatriates’ ability and motivation to engage in RKT. The aim of this thesis is to gain more information regarding what aspects affect RKT and how it can be enhanced. A qualitative research is conducted with nine repatriates, who all work in the same Finnish company. The results indicate that RKT is not actively practiced in the company. Additionally, it is found that repatriate support practices are not actively utilized in the company. The results high-light that repatriates’ ability to engage in RKT is tightly connected to the position or role they have in the organization. However, regardless of the current state of repatriation support practices in the company, a majority of the repatriates appear to be motivated to engage in RKT. Instead, the lack of suitable knowledge sharing platform and a clear need for knowledge, which originates from the company itself, appear to have a greater impact on why RKT has not been an active part of the company’s functions.
Keywords: repatriation; repatriate knowledge transfer; knowledge management; knowledge sharing; human resource management; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business